Determinants for coopetition strategies of international joint ventures in high-speed railway projects - Niu, Yanliang; Zhao, Dan; Deng, Xiaopeng; Lu, Ruoyu; Zhao, Xianbo (Journal of Civil Engineering and Management, 2021)
International joint ventures (IJVs) have become a significant mode of exploiting high-speed railway (HSR) overseas market for contractors. This study is devoted to identify the determinants for the coopetition strategies of IJVs in the HSR projects, as well as the interactive paths. On the base of a thorough literature review and the pilot study with five industry experts, 22 determinants were identified and packaged into six groups covering the three levels (including macro, firm, and project levels). Meanwhile, the interactive paths amongst the six groups were proposed. A questionnaire survey was performed with 210 practitioners experienced in IJVs in HSR projects to assess the significance of the factors, and 113 valid questionnaires were received. Based on the collected data, six groups of 22 determinants and nine interactive paths were verified by applying partial least-squares structural equation modeling technology. Specifically, these significant paths could be classified into two categories, namely the coopetition-capability oriented paths, and the coopetition-relationship oriented paths. The findings of this paper are conductive to expand the knowledge on coopetition and provide a useful reference for the members of IJVs in HSR projects to accomplish coopetition strategies from pre-project phase, the implementation phase, to post-project phase.